EXPLORING THE GRAPHS OF FUNCTIONS USING THE JIGSAW APPROACH - VIJAYAN, Vijayanthi; SHAHRILL, Masitah; ABBAS, Nor ‘arifahwati; TAN, Abby (The Eurasia Proceedings of Educational and Social Sciences, 2016)
Cooperative learning is a strategy that involves students working together towards achieving a common goal. This learning technique can be carried out in various ways and one such method is by the jigsaw approach. In the jigsaw approach, students become experts in a particular concept and then share their knowledge with other group members. The purpose of this study is to investigate how effective the jigsaw approach is in improving students’ performance levels in Mathematics, in particular, in the topic of graphs of functions. This mixed method action research study involves two cycles, conducted in two different local government schools in Brunei Darussalam. Cycle 1 involves a Mathematics class of 19 students and Cycle 2 with 25 students, and both at the Year 10 level. A pre-test and post-test design was used for this purpose. Students’ perceptions on cooperative learning were also studied. The results of this study suggest that the jigsaw approach does have a positive effect on students’ performance levels in Mathematics. Cooperative learning needs to be practiced more in classrooms as it helps in the development of 21st century skills for the students